Analytical Investigation of Tension Loaded Deformed Rebar Anchors in Concrete - Sandip Chhetri; Rachel A. Chicchi (CivilEng, 2021)
Experimental testing of deformed rebar anchors (DRAs) has not been performed extensively, so there is limited test data to understand their failure behavior. This study aims to expand upon these limited tests and understand the behavior of these anchors, when loaded in tension. Analytical benchmark models were created using available test data and a parametric study of deformed rebar anchors was performed. Anchor diameter, spacing, embedment, and number of anchors were varied for a total of 49 concrete breakout simulations. The different failure modes of anchors were predicted analytically, which showed that concrete breakout failure is prominent in the DRA groups. The predicted concrete breakout values were consistent with mean and 5% fractile concrete capacities determined from the ACI concrete capacity design (CCD) method. The 5% fractile factor determined empirically from the simulation results was kc = 26. This value corresponds closely with kc = 24 specified in ACI 318-19 and ACI 349-13 for cast-in place anchors. The analysis results show that the ACI CCD formula can be conservatively used to design DRAs loaded in tension by applying a kc factor no greater than 26.